Restitution As A Form Of State Responsibility Toward Child Victims Of Sexual Abuse Crimes - Muhammad Eri Fatriansyah; Heni Siswanto; Muhtadi; Ahmad Irzal; Rini Fathonah (Yayasan pendidikan dzurriyatul Quran, 2026)
The criminal act of sexual abuse against children constitutes a serious offense that causes long-term traumatic impacts on victims. The state bears a constitutional obligation to protect and restore the rights of child victims of sexual crimes through restitution mechanisms. This study examines the implementation of restitution as a manifestation of state responsibility within the Indonesian criminal justice system. The objectives of this research are to identify the juridical foundations of restitution for child victims of sexual abuse, analyze its implementation mechanisms, and evaluate the obstacles in fulfilling restitution rights. This research employs a normative juridical approach through the analysis of statutory regulations, court decisions, and relevant legal literature. The findings indicate that although restitution has been regulated under Law Number 31 of 2014 concerning the Protection of Witnesses and Victims and Law Number 35 of 2014 concerning Child Protection, its implementation continues to face substantive and procedural challenges. The primary obstacles include limited understanding among law enforcement officials, the complexity of application procedures, constraints on state budget allocation, and the low level of victim awareness regarding restitution rights. In conclusion, restitution is a vital instrument for victim recovery and reflects the state’s responsibility; however, it requires systemic reform through procedural simplification, capacity building for law enforcement personnel, adequate budget allocation, and extensive public dissemination.